The Influence of Video Marketing and Digital Storytelling on Perceived Increase in Consumer Purchase Intention through Brand Engagement: A Study on MSMEs - Frans Sudirjo; Suherlan; Moses Odhiambo Okombo; Syamsuri (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2026)
This study investigates the influence of video marketing and digital storytelling on consumer purchase intention through brand engagement among MSMEs in Jakarta. The research is grounded in the Theory of Planned Behavior (TPB) and Customer Engagement Theory, which together provide the conceptual framework for understanding how visual and narrative-based digital content affects consumer attitudes, engagement, and behavioral intention. The study is driven by real-world challenges faced by MSMEs, particularly the widespread use of video and storytelling content that often fails to generate meaningful engagement or improve sales due to limited emotional depth, weak narrative authenticity, and low digital literacy among business actors. Using a quantitative approach and SEM–PLS analysis on data obtained from 100 MSME respondents, the findings reveal that both video marketing and digital storytelling significantly enhance brand engagement. However, only video marketing shows a significant direct effect on purchase intention, while digital storytelling demonstrates no significant impact and even indicates a negative tendency. Additionally, brand engagement does not serve as a significant mediator for either content strategy. These results highlight that exposure to video or narrative content alone is insufficient without strong contextual relevance and emotional resonance. The study contributes to the development of TPB and Customer Engagement Theory by showing that engagement and intention require deeper psychological processes beyond content exposure and provides practical insights for MSMEs to produce more authentic, emotionally compelling, and culturally aligned digital content.